PROTECTION OF AIR PASSENGER RIGHTS IN AIR LAW: A REVIEW PF CONSUMER LAW PERSPECTIVES - Ardian, Dede (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The problem in this study is the regulation of legal protection for passengers who use scheduled national commercial air transportation services, as well as legal remedies for passengers who are harmed by scheduled national commercial air transportation companies. This study is normative legal research conducted by tracing the legislation relating to legal protection against commercial air transport passengers. Normative-qualitative analysis of data. The results showed that in the positive legal order in Indonesia, there are several laws and regulations relating to legal protection for air transportation passengers, namely: Law No. 15 of 1992, Law No. 8 of 1999, and Government Regulation No. 40 of 1995. The regulated legal protection material includes the responsibility of the air carrier company, which consists of responsibility for passengers, responsibility for goods, responsibility for delays (delays), and insurance responsibility. Considering that the legal instruments relating to the protection of air transportation passengers are old, it is necessary to review the materials or substances because they are no longer in accordance with the times (up to date), especially regarding the provisions of the Compensation Value. Therefore, it is expected that the legislator will immediately form a new law that accommodates the interests of the community as consumers.